Integration of Collective Knowledge into Simulative Urban Modelling (EAAE Annual Conference Proceedings, 2023)
The modernistic urbanism treated cities as top-down way constructed machines and caused a significant transformation form city of places to city of spaces which could not be effectively addresses even if New Urbanism or related models are formally employed in urban planning. It should be recognized that urban place creation and placemaking is not possible without effective public participation which because of various reasons, especially in Lithuania, is not effective. The presented research is based on combination of two approaches while working in historical Šančiai neighborhood community in Kaunas.